Multi-disciplinary conceptual design of future jet engine systems - Kyprianidis, Konstantinos G. (Cranfield University, 2010)
This thesis describes various aspects of the development of a multi-disciplinary aero engine conceptual design tool, TERA2020 (Techno-economic, Environmental and Risk Assessment for 2020), based on an explicit algorithm that considers: engine performance, engine aerodynamic and mechanical design, aircraft design and performance, emissions prediction and environmental impact, engine and airframe noise, and production, maintenance and direct operating costs. As part of this research e ort, a newly-derived semi-empirical NOx correlation for modern rich-burn single-annular combustors is proposed. The development of a numerical methods library is also presented, including an improved gradientbased algorithm for solving non-linear equation systems. Common assumptions made in thermo- uid modelling for gas turbines and their e ect on caloric properties are investigated, while the impact of uncertainties on performance calculations and emissions predictions at aircraft system level is assessed. Furthermore, accuracy limitations in assessing novel engine core concepts as imposed by current practice in thermo- uid modelling are identi ed. The TERA2020 tool is used for quantifying the potential bene ts from novel technologies for three low pressure spool turbofan architectures. The impact of failing to deliver speci c component technologies is quanti ed, in terms of power plant noise and CO2 emissions. To address the need for higher engine thermal e ciency, TERA2020 is again utilised; bene ts from the potential introduction of heat-exchanged cores in future aero engine designs are explored and a discussion on the main drivers that could support such initiatives is presented. Finally, an intercooled core and conventional core turbofan engine optimisation procedure using TERA2020 is presented. A back-to-back comparison between the two engine con gurations is performed and fuel optimal designs for 2020 are proposed. Whilst the detailed publications and the work carried out by the author, in a collaborative e ort with other project partners, is presented in the main body of this thesis, it is important to note that this work is supported by 20 conference and journal papers.